KONDISI TEGAKAN TINGGAL DI KAW ASAN DUA PERUSAHAAN HUTAN DI RIAU - Sona Suhartana; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1996)
Log  skidding  activities  using  tractors  usually  caused  high  residual stand  damages.  To reduce the residual stand damages, the factors  influencing them must be identified. A study was carried out at two forest  concessions in Riau in  1995. The aims of the study are :  1) to find  the level  of  residual  stand  damages  caused  by felling  ang skidding,  2) to  identifY   the  factors influancing the  residual  stand  damages  and  3) to find  the way of  reducing  residual stand damages.Data collected  were the number  of  felled  tress,  trees with diameter  20 cm and  up and damaged trees.  The data was analysed by using the multiple regression.The results of the study show : 1)  The average of residual stand damages caused by fellingis 11.5 %; 2) The average of residual stand damages caused by skidding  is 15.4  %; and 3) The influence of the number of felled  tress, stand density and the slope were highly  significant to residual stand damages.Knowing the factors  influencing  the residual stand damages, ones should be easy to find the way of reducing  that damages.Key words :   felling, skidding, felled trees, residual  stand damage